Cravnitel'nyi analiz effektivnosti razlichnykh metodov relaksatsii myshts - Pismenski, V. V.; Lubbardy, M. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The authors' result of the comparative analysis has shown that the degree of various methods of muscles' relaxation efficacy depends on the type of the muscle first of all. However, the advantage should be given up to the classical massage, especially with use of the special oils and creams.